Cross-Frequency Coupling in Developmental Perspective - Knyazev, Gennady G.; Savostyanov, Alexander N.; Bocharov, Andrey V.; Tamozhnikov, Sergey S.; Kozlova, Elena A.; Leto, Irina V.; Slobodskaya, Helena R. (Frontiers in Human Neuroscience, 2019)
It is generally assumed that different EEG frequency bands are somehow related to different computational modes in the brain. Integration of these computational modes is reflected in the phenomenon of cross-frequency coupling (CFC). On slow temporal scales, CFC may reflect trait-like properties, which posits a question of its developmental trends. This is the first study that explored source-level CFC measures in developmental perspective using both cross-sectional and longitudinal designs. CFC measures demonstrated good test-retest stability and proved to be higher in adults in cortical areas participating in sensory-motor integration, response inhibition, and attentional control. In children, greater CFC was observed in parietal regions involved in self-centered cognition. Over the period from 7 to 10 years, CFC demonstrated nonlinear growth trajectories. Introversion was associated with higher CFC in cortical areas related to emotion, attention, and social cognition implying that the association between introversion and CFC appears early in the development.